Efficiency Performance of Industrial Innovation System of China Brand Automobile - Jianglin, Jiang; Jianglin, Jiang (UNIVERSITI MALAYSIA SARAWAK PRESS, 2024)
In 2009, China has become the largest automobile production and sales country in the world. However, China automobile industry presents a large but not strong situation, that is the market share of own brand automobile is not high, and the situation of relying on foreign brands and technology is still serious. Based on the innovation system of automobile industry, this study analyzes the problem of “large but not strong” of China automobile industry. The aim of this study is to investigate the efficiency performance of the innovation system of China automobile industry from 2001 to 2021. The DEA-VRS, DEA-CRS method and DEA-Malmquist index model were used to evaluate the innovation efficiency of China brand automobile industry. The technical efficiency, pure technical efficiency, scale efficiency, total factor productivity, comprehensive technical efficiency, and technological progress index are calculated, respectively. It also explores the determinants of innovation system's efficiency. The conclusion of this study is that, from the perspective of 24 regions, there are obvious spatial imbalances in the efficiency development of China own brand automobile industry’s innovation system. From a national perspective, there is no significant upward or downward trend in the efficiency of the innovation system in the own brand automobile industry. The total factor productivity and comprehensive technical efficiency show no significant trend and do not exceed 1.0, while the technology progress index shows a fluctuating upward trend, with values higher than 1.0 throughout the entire sample period. In terms of influencing factors, there are several identical ones that have different impacts on efficiency and productivity, respectively. The policy recommendations of this study are that own brand automobile enterprises should strengthen technological research and development, choose the optimal development model. The government should increase investment in the research and development of own brand automobile enterprises, establish scientific systems, promote the effective combination of industry, academia, and research, carry out top-level design to enhance the independent innovation drive of state-owned automobile groups.